2011
DOI: 10.3346/jkms.2011.26.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Pneumococcal Carriage of Children Attending Day Care Centers in Korea: Comparison between Children Immunized with 7-valent Pneumococcal Conjugate Vaccine and Non-immunized

Abstract: To confirm the effect of 7-valent pneumococcal conjugate vaccine (PCV7), pneumococcal nasopharyngeal (NP) carriage was compared between vaccinated (3 + 1 doses PCV7) and non-vaccinated children. Vaccinated subjects were recruited from highly vaccinated regions (≥ 60%), Seoul and Incheon whereas control subjects were recruited from Jeju Island where vaccination rates are low (< 15%). NP swabs were obtained from 400 children aged 18-59 months. Serotype and antibiotic susceptibility was analyzed. Pneumococcal car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Sixteen Korean isolates were obtained from the nasopharynges (NP) of healthy children (less than 5 years old) attending daycare centers (DCCs) in 2008 (43). Twenty-six Brazilian isolates were obtained from the NP of children (less than 5 years old) attending municipal DCCs in 2005 (31, 45).…”
Section: Methodsmentioning
confidence: 99%
“…Sixteen Korean isolates were obtained from the nasopharynges (NP) of healthy children (less than 5 years old) attending daycare centers (DCCs) in 2008 (43). Twenty-six Brazilian isolates were obtained from the NP of children (less than 5 years old) attending municipal DCCs in 2005 (31, 45).…”
Section: Methodsmentioning
confidence: 99%
“…PCV7 was recently licensed and introduced into the Asian countries of South Korea (2003) (15). Although the PCV7 vaccination rate in most Asian countries has not been investigated, it seems to be very low in most Asian countries due to lack of awareness among both the general public and physicians and due to vaccination cost, while the vaccination rate in children under 5 years of age is relatively high in South Korea (over 60% in urban areas) (12). Vietnam, where PCV7 was not available at the time of the study, showed the highest coverage rate of PCV7 serotypes in this study, while the coverage rates have decreased in most other Asian countries compared with our previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of invasive pneumococcal disease (IPD) has significantly decreased since the introduction of conjugate vaccines based on seven, and more recently, 13 capsular polysaccharides (5, 6). However, the incidences of carriage and IPD have increased for some capsular serotypes not covered by the conjugate vaccines (7, 8), and the incidence of carriage has increased for nonencapsulated and nontypeable pneumococci (9, 10). …”
Section: Genome Announcementmentioning
confidence: 99%